Performance Evaluation of the WSN Routing Protocols Scalability. (28th January 2009) - Alazzawi Alazzawi, L. L.; Elkateeb Elkateeb, A. A.
Abstract : Scalability is an important factor in designing an efficient routing protocol for wireless sensor networks (WSNs). A good routing protocol has to be scalable and adaptive to the changes in the network topology. Thus scalable protocol should perform well as the network grows larger or as the workload increases. In this paper, routing protocols for wireless sensor networks are simulated and their performances are evaluated to determine their capability for supporting network scalability.